Predictive factors and pharmacological preventive interventions for atrial fibrillation after aortic valve replacement - Lu Chen; Yu Liu; Junmei Ge (Journal of Cardiothoracic Surgery)
Abstract Objective This study aims to investigate the predictive factors for postoperative atrial fibrillation (POAF) following aortic valve replacement (AVR) and evaluate the preventive effect of combined atorvastatin and metoprolol therapy on POAF. Methods This study employed a mixed design of retrospective cohort analysis and prospective randomized controlled trial, including 268 patients who underwent isolated AVR from January 1, 2022, to March 31, 2024. The 168 patients from January 1, 2022, to May 31, 2023, were analyzed for POAF predictive factors, while 100 patients from June 1, 2023, were included in the prospective trial. The intervention group (n = 50) received combined atorvastatin and metoprolol treatment starting 7 days before surgery. Results Multivariate logistic regression analysis identified age (OR = 1.12, 95% CI: 1.04–1.20, p = 0.003), history of stroke (OR = 10.94, 95% CI: 1.32–90.66, p = 0.027), EuroSCORE II (OR = 2.90, 95% CI: 1.61–5.20, p < 0.001), NT-proBNP level (OR = 1.002, 95% CI: 1.001–1.004, p = 0.009), hs-CRP level (OR = 1.55, 95% CI: 1.16–2.07, p = 0.003), and operation time (OR = 1.02, 95% CI: 1.01–1.04, p = 0.008) as independent predictors of POAF. Pharmacological intervention significantly reduced POAF incidence (p = 0.005) and shortened hospital stay (p < 0.001), ICU stay (p = 0.002), and mechanical ventilation time (p < 0.001). The AUC of the predictive model was 0.952, with a calibrated C-statistic of 0.904. Decision curve analysis demonstrated significant clinical utility across multiple risk thresholds. Conclusion Age, history of stroke, EuroSCORE II, NT-proBNP and hs-CRP levels, and operation time are independent predictors of POAF. Combined preventive treatment with atorvastatin and metoprolol reduced POAF incidence and postoperative hospital stay, showing promising clinical application prospects.